2016
DOI: 10.2174/1874120701610010082
|View full text |Cite
|
Sign up to set email alerts
|

Telecare Services for Elderly: Predictive Factors of Continued Use Intention

Abstract: Background:Several countries have recently attempted to implement telecare information technology to provide health care to older adults. This study applied self-determination theory (autonomy, relatedness, and competence) and the theory of planned behavior (subjective norm, perceived behavioral control, and attitudes toward using tools) to investigate a theoretical model for explaining the predictive factors influencing the intention of elderly patients to continue using telecare services.Methods:Elderly pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 50 publications
1
3
1
Order By: Relevance
“…According UTAUT, social influence is a significant predictor in mandatory settings only and studies did not find an association between social influence and intention to use eHealth among older adults ( 11 , 12 , 14 ) . However, our study and others did find an association ( 10 , 32 35 ) . This might be explained by the way social influence is operationalised in studies, or by the suggestion that the role of social influence is dependent on the context ( 12 , 14 ) .…”
Section: Discussioncontrasting
confidence: 97%
“…According UTAUT, social influence is a significant predictor in mandatory settings only and studies did not find an association between social influence and intention to use eHealth among older adults ( 11 , 12 , 14 ) . However, our study and others did find an association ( 10 , 32 35 ) . This might be explained by the way social influence is operationalised in studies, or by the suggestion that the role of social influence is dependent on the context ( 12 , 14 ) .…”
Section: Discussioncontrasting
confidence: 97%
“…Thus, Hypothesis 2 was supported. Similar to the results of previous studies, family and friends can influence the intention to use mobile health technology, and a significant correlation exists between social influence and continuous usage intention [23,66]. Liu et al [24] also found that social influence positively affected the elderly' s sharing behavior of health information in China.…”
Section: Principal Findingssupporting
confidence: 76%
“…However, such programming arises from the need for services that can provide care for frail elderly people while allowing them to maintain their autonomy as long as possible. 9,10 Among the new strategies for elderly care, telemedicine services are emerging as a viable approach, e.g. by allowing some physiological parameters to be measured directly at home (using simple portable detection devices) and sent automatically to the referring physician.…”
Section: Introductionmentioning
confidence: 99%